Distress, depression, human right abuse and sexual risk behavior to HIV infection among men WHO have sex with men in selected districts of Nepal. - Singh, Rakesh (2010)
ABSTRACT: The objectives of the study were to assess and compare the level of depression between men who have sex with men and general population, assess correlates of distress and depression, frequency of human rights abuses and sexual risk behavior to HIV infection, and to find out the relationship of depression and sexual risk behavior in men who have sex with men in selected districts of Nepal. The study was analytical cross-sectional in design. The study sample was 170 chosen conveniently from five district of Nepal. Equal numbers of general population (170 heterosexual men) to men who have sex with men of similar age were also studied to compare depression rates between them. the data collection tool was developed in consultation with five experts from the related fields establishing content validity and reliability of the tool was established by test-retest method. Data analysis was done by using both descriptive and inferential statistics using MS Excel 2007. Men who have sex with men had more distress and depression as compared to heterosexual men [t cal= 14.99*, df (338), tcritical =1.98, p<0.05]. Distress and depression among men who have sex with men were found to be independent of their age and family income [x2age=1.86, x2income=2.43), p>0.05] and dependent on education and living status [x2education=62.85*, x2 living status=2.43*, p<0.05]. Similarly large percentage of men who have sex with men were found to be the victims of human rights abuses like being raped (61%), sexually abused during childhood (59%), blackmailed (59%), beaten up by police official (60%), being teased by people (65.9%). They were found to be involved in high risk sexual behavior like multiple sex partners, sexual activity with partner of unknown HIV status, and intercourse without use of condom. There was a positive significant correlation between the depression and sexual risk behavior among them [r=0.63*, p<0.05]. The first and the most important thing to be done is to bring positive change in attitudes and resultant behavior towards them. They need a life with equal human rights as the rest of the population, not only on paper but in practice; a life without discrimination, hatred and social stigma against their sexuality; a life of respect and dignity. same-sex marriage should be legalized so that for sexual need such minority group do not involve themselves in commercial sex leading to risks of HIV and AIDS and mental health problems. Follow-up study is recommended along with further researches among men who have sex with men regarding issues like predictor of depression; child sexual abuse, depression and suicide; condom and lubricant use, substance abuse; depression and HIV risk behavior; including measures of sexual orientation.